2001
DOI: 10.1103/physrevb.64.085421
|View full text |Cite
|
Sign up to set email alerts
|

Size effect in self-trapped exciton photoluminescence fromSiO2-based nanoscale materials

Abstract: Direct evidence for a size effect in self-trapped exciton ͑STE͒ photoluminescence ͑PL͒ from silica-based nanoscale materials as compared with bulk type-III fused silica is obtained. Two kinds of mesostructures were tested: ͑1͒ silica nanoparticle composites with primary particle size of 7 and 15 nm, ͑2͒ ordered and disordered mesoporous silicas with pore size ranging from ϳ2 to ϳ6 nm and wall thickness ϳ1 nm. The PL was induced by the two-photon absorption of focused 6.4 eV ArF laser light with intensity ϳ10 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
52
0
1

Year Published

2005
2005
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 115 publications
(57 citation statements)
references
References 35 publications
(106 reference statements)
4
52
0
1
Order By: Relevance
“…The energy gained from laser heating of the exciton increases with decreasing nanosolid diameter in an exp(1/R) form. Based on the analysis, Glinka et al [73] indicated that the size-dependent PL blueshift of a nanosolid in general does not need to be related always to the QC effect.…”
Section: Other Schemesmentioning
confidence: 99%
See 3 more Smart Citations
“…The energy gained from laser heating of the exciton increases with decreasing nanosolid diameter in an exp(1/R) form. Based on the analysis, Glinka et al [73] indicated that the size-dependent PL blueshift of a nanosolid in general does not need to be related always to the QC effect.…”
Section: Other Schemesmentioning
confidence: 99%
“…A free-exciton collision model [73] proposed for the PL blueshift suggests that the E G expansion arises from the contribution of thermally activated phonons in the grain boundaries rather than the QC effect. During PL measurement, the excitation laser heats the free-excitons that then collide with the boundaries of the nanometer-sized fragments.…”
Section: Other Schemesmentioning
confidence: 99%
See 2 more Smart Citations
“…The most widespread, simple theoretical framework to study the influence of confinement effects and, particularly, the primary particle size influence in exciton energy, is the so-called effective-mass approximation (EMA). 4,48 Other theories as the free-exciton collision model (FECM) 49 have been implemented and although are much less utilized may become alternatives in the near future for massive use. The EMA theory assumes parabolic energy bands, infinite confining potential at the interface of the spherical semiconductor particle, and limits main energy terms to electron-hole interaction energy This indicates a blue shift of E(R) as a function of R -2 .…”
Section: Optical Absorptionmentioning
confidence: 99%